Bazedoxifene blocks AGEs-RAGE-induced superoxide generation and MCP-1 level in endothelial cells. (June 2015) - Ishibashi, Y.; Matsui, T.; Ueda, S.; Fukami, K.; Okuda, S.; Ohta, H.; Yamagishi, S.
Abstract Advanced glycation endproducts (AGEs) and their receptor (RAGE) play a role in vascular complications in diabetes. We have previously shown that 17β-estradiol at 10 nmol/l, a nearly identical plasma concentration to that during mid-pregnancy, up-regulates RAGE expression in endothelial cells. The finding might suggest the involvement of 17β-estradiol in the deterioration of vascular complications in diabetes during pregnancy. However, the effects of the selective estrogen receptor modulator, bazedoxifene, on oxidative and inflammatory reactions in AGEs-exposed endothelial cells remain unknown. In this study, we addressed the issue. Ten nmol/l 17β-estradiol increased RAGE and monocyte chemoattractant protein-1 (MCP-1) gene and protein expression in human umbilical vein endothelial cells (HUVECs), both of which were blocked by 10 nmol/l bazedoxifene. Bazedoxifene at 10 nmol/l also significantly inhibited the AGEs-induced superoxide generation, RAGE and MCP-1 gene and protein expression in HUVECs. The present study suggests that blockade of the AGEs–RAGE axis by bazedoxifene might be a novel therapeutic target for preventing vascular damage in diabetes, especially in postmenopausal women.